PERAN E-COMMERCE DALAM KEWIRAUSAHAAN DI ERA SOCIETY 5.0 - Vera Maria (Sekolah Tinggi Pariwisata Mataram, 2023)
Technological disruption is causing unprecedented changes in how every aspect of human life is conducted. The economy and social interactions are greatly affected by these changes. Therefore, the government must intervene to accelerate the use of technology for society. Technology is a tool to make work easier. Current technological developments have become something that is the main need for humans in completing work. Technological developments started from the Industrial Revolution 1.0 to the Industrial Revolution 4.0. In addition, changes in human behavior are also marked by the development of Society 5.0. The impact of technological developments greatly influences the behavior of the Economic Community, especially in e-commerce activities. The development of e-commerce is dominating in Indonesia, especially in increasing interest in entrepreneurship. The research methodology is based on theoretical and conceptual experience, collection of information and data related to entrepreneurship and e-commerce, and additional data from books, journals or other sources.